Divorce Petition Against Drug User Husband: Case Study of Kuala Simpang Syar'iyah Court Decision, Aceh Tamiang - Devy, Soraya; Amrullah, Amrullah; Zulfiana, Utari (El-Usrah: Jurnal Hukum Keluarga, 2023)
A wife can file for divorce for a variety of reasons, one of which is because her husband is involved in a drug case. The purpose of this study is to determine the factors considered by Kuala Simpang Syar'iyah Court judges in deciding divorce cases involving drug-user husbands from the standpoint of Islamic law. This study employs empirical research methodologies that are examined using Islamic legal philosophy. This case study examines the judge's ruling at the Kuala Simpang Syar'iyah court in Aceh Tamiang. The court bases its judgment on the state of being detrimental in the family, as the decision of the wife's petition against her drug-using husband is not governed by any law or other regulations. According to the Maliki and Hambali Schools of Thought, a wife may file for divorce from her drug-using husband before a court under Islamic family law. Because the plaintiff and defendant's domestic lives were no longer harmonious since her husband began using drugs, her husband frequently became violent when under the influence of drugs. Thus, the judge's considerations align with Islamic law norms aimed at promoting and protecting the wife and family.